PENGARUH PROGRAM ACARA TALKSHOW DR OZ INDONESIA TERHADAP PENGETAHUAN MAHASISWA DALAM DUNIA KESEHATAN DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Rahel Kristiani Simamora; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Programs are all things that broadcast stations show to meet their Audience needs. One of the programs on television is talk show. The talk show program that the public is interested in is DR OZ Indonesia, which provides information about the world of health. This research is based on Stimulus-Response-Response theory. The message (Stimulus) in this research is the information delivered by the speakers in DR OZ Indonesia program, the communicant (organism) of the students of the Faculty of Social and Political Sciences of the University of Riau while the Response (Response) is the impressive DR OZ Indonesia show to the students watching behavior tips given by the resource person.The method used in this study is quantitative methods, data collection techniques in this study using questionnaires. The number of samples for this study as many as 96 respondents. Samples using Accidental Sampling.To know how big the influence of these two variables, the researchers used a simple linear analysis. For data processing questionnaire, done by using Program Statistic Product And Service Solution (SPSS) Windows version 19.The results of research on the influence of DR OZ Indonesia program with indicators (Hosts, Event Formats, Event Content, Frequency, Duration) to health knowledge (Know, Understanding 65, Application, Analysis, Evaluation) students at the Faculty of Social and Political Sciences, Riau University obtained value regression coefficient in this study is Y = 21.791 + 0.606 X with a significance level of 0.000 smaller than α = 0.05. This means that there is the influence of DR OZ Indonesia program to the health knowledge of students in the Faculty of Social and Political Sciences, Riau University obtained by 18.6% and fall into the category of weak influence. The percentage indicates that DR OZ Indonesia program influences consumptive behavior thus H0 is rejected and Ha accepted.Keyword : programs, dr oz indonesia, health knowledge